El Niño impacts in the Inkomati catchment - Montes, Carlo (International Food Policy Research Institute, 2023)
Near normal temperatures are predicted for the Inkomati catchment from July to December 2023. Near normal rainfall amounts are predicted for the Inkomati catchment from July to December 2023. A reduction in rainfall, higher than usual temperatures and evaporative demand. Drought conditions induced by the 2023 strong El Niño event are expected for the Inkomati catchment from January to March 2024 and likely until the next wet season.